Awareness level among valuation practitioners on the use of the Geographic Information System (GIS) in real estate valuation / Nur Izzati Ridzuan - Ridzuan, Nur Izzati (2023)
The property valuation process has long relied on manual methods, leading to energy-consuming, time-consuming, and costly procedures. However, the emergence of Geographical Information Systems (GIS) has transformed this landscape, offering enhanced data precision and effectiveness in real estate valuation. Yet, the emphasis of GIS in real estate valuation has been limited, necessitating further investigation. The study explores the potential use of GIS in real estate valuation through existing literature, identifying four main themes: data visualization, price prediction models, mass valuation, and cloud storage, highlighting its versatility and potential to revolutionize traditional valuation practices. An online questionnaire survey revealed a significant lack of awareness among practitioners regarding GIS and its benefits, necessitating targeted awareness campaigns and comprehensive training programs. Integrating GIS with traditional methods can lead to more well-informed valuation practices and better decision-making processes.